Study on vitamin D2 stability in dried mushrooms during drying and storage. (15th May 2016) - Sławińska, Aneta; Fornal, Emilia; Radzki, Wojciech; Skrzypczak, Katarzyna; Zalewska-Korona, Marta; Michalak-Majewska, Monika; Parfieniuk, Ewa; Stachniuk, Anna
Highlights: The amount of vitamin D2 decreases during storage of hot-air dried mushrooms. Fresh and dried mushrooms have the ability to produce vitamin D2 under the UVB irradiation. UVB-induced production of D2 in dried mushrooms reaches the level of up to 119.21 μg/g dw. Abstract: The main objective of this work was to determine the stability of vitamin D2 in dried mushrooms Agaricus bisporus, Pleurotus ostreatus and Lentinula edodes during storage, as well as to examine the possibility of inducing vitamin D2 production in dried mushrooms by UVB irradiation. After 1.5 year storage of dried mushrooms, the level of vitamin D2 in button mushrooms was found to be 6.90 μg/g dw, which is a 48.32% of initial level of vitamin D2 . In the case of dried oyster and shiitake mushrooms there was a decrease to the level of 66.90% and 68.40%, respectively. It was determined that dried mushrooms can produce ergocalciferol under UVB irradiation. The highest content of vitamin D2 was observed in A. bisporus . Freeze-dried A. bisporus contained from 42.08 to 119.21 μg/g dw and hot-air dried mushrooms contained from 21.51 to 81.17 μg/g dw vitamin D2 .